More Time Spent in Sedentary Behaviors is Associated with Higher Plantar Pressures in Older Women - Kasović, Mario; Štefan, Lovro; Zvonař, Martin (International journal of environmental research and public health, 2020)
Background: Although obesity has been consistently correlated with higher plantar pressure during the lifespan, to date little evidence has been provided regarding of how domain-specific and total sedentary behaviors may be correlated with plantar pressures. Moreover, high peak plantar pressures have been consistently associated with foot pain and discomfort, which prevent individuals from being physically active. Therefore, the main purpose of the study was to explore the correlations between time spent in sedentary behaviors and plantar pressures. Methods: We recruited 120 older women aged ≥60 years. To assess the time spent in different domains of sedentary behavior, we used the Measure of Older Adults' Sedentary Time (MOST) questionnaire. Peak pressures beneath forefoot, midfoot and hindfoot were measured with a Zebris pressure platform. Results: In the unadjusted model, peak pressures were significantly correlated with almost all domain-specific sedentary behaviors (r = 0.15-0.41). Total time spent in sedentary behaviors was significantly correlated with forefoot (r = 0.40, p < 0.001), hindfoot (r = 0.31, p < 0.001) and total peak plantar pressure (r = 0.40, p < 0.001). In a model adjusted for age, the risk of falls, foot pain and gait velocity, similar significant correlations between sedentary behaviors and plantar pressures remained. Conclusions: Our study shows moderate correlation between domain-specific and total time spent in sedentary behaviors and plantar pressure beneath different foot regions in a sample of older women.
Keywords: senioři; sedavý životní styl; Obesity; Sedentary Behavior; chůze (způsob); forces; Middle Aged; Pain; tlak; Pressure; Foot; ženské pohlaví; Humans; lidé středního věku; obezita; sedentariness; relation; Female; Aged; bolest; Gait; noha (od hlezna dolů); lidé; foot